Exploring the Impact of Access to Information Laws on Corruption in Malawi - Lloyd George Banda; Kelvin Ryna Chilala; Innocent Kazembe Chirwa; Emmanuel George Yusufu (Politikon)
Malawi's access to information (ATI) law culminated in an advocacy of over two decades, with political leaders opposing and tactically delaying its implementation. While politicians construed the law as a media law, the core policy belief of the advocacy coalition was to eliminate the culture of secrecy in public offices and ensure government openness and accountability, with the control of corruption as a means to an end. This study employs a time-series positivistic approach to analyse data from 1996 to 2022. Additionally, the study employs the autoregressive distributed lag (ARDL) approach, bounds cointegration, and the overall error correction model (VECM) to establish the long-run relationship between public access to information and corruption indices. Parameter estimates reveal that any initiative to boost public access to information will reduce corruption by 0.374%, with the impact manifesting after two years. In the long run, however, improving Access to Information laws reduces corruption by 0.264%, ceteris paribus. The results of this study imply that the Advocacy Coalition Framework (ACF) holds true in its hypothesis that the altruism of advocacy groups should not be precluded. Indeed, without at least one shared policy core belief, it would have been hard or otherwise impossible for professionally varied actors to be glued together for a frustrating period of 22 years in pursuit of access to information law.